Chloroplast genome evidence in assessing the taxonomic status of Astragalus zerabulaki Popov (Fabaceae), an endemic of Uzbekistan - Bobur, Karimov; Ziyoviddin, Yusupov; Ergashali, Ruzimatov; Farkhod, Karimov; Komiljon, Tojibaev (Phytotaxa, 2026)
The taxonomic position of Astragalus zerabulaki Popov, a narrowly distributed species from Uzbekistan, has long been controversial. To clarify its systematic status, we sequenced and compared the complete chloroplast genomes and nuclear ribosomal regions of A. zerabulaki and A. rumpens. The complete chloroplast genome of A. zerabulaki (123,542 bp; GC 34.0%) differs slightly from that of A. rumpens (123,551 bp; GC 34.1%) and exhibits 614 nucleotide variations, including 491 indels and 123 SNPs. Sliding-window analysis identified several hypervariable regions (accD–ycf4, rps8–rpl14, ycf2–ndhB), while SSR analysis revealed a unique C/G mononucleotide repeat in A. zerabulaki. Phylogenetic analyses based on plastid and nuclear datasets recovered A. zerabulaki, A. rumpens, A. agrestis, and A. arbuscula as a well-supported clade. These molecular distinctions confirm A. zerabulaki as a genetically and geographically distinct species within section Chaetodon Bunge.